Elementos de La Comunicación Entre una Persona con Trauma Craneoencefálico y Su Cuidador Familiar (2016)
This is a qualitative research, in which the analysis of the elements of the existing communication between a person who has suffered Traumatic Brain Trauma and their family caregiver. The population is taken as a total of five people who have suffered TBI and their family caregiver and through an interview script carried out with the two subjects, it is achieved Identify and describe the elements of communication present in the two people. The Research results reveal that communication is an interactional process characterized in these subjects by the presence of axioms given in that daily interaction, and in pathological communication at content and relationship levels, in digital and analog communication